Homicídios revestidos de legalidade : uma análise do discurso oficial acerca da violência policial na cidade Porto Alegre no período de 2005 a 2010 - Gonçalves, Paula Garcia (2018)
This dissertation is inserted in the research line “Violence, Crime and Public Safety”, under the guidance of Prof. Dr. Ricardo Jacobsen Gloeckner, and has as objective the analisys of the official discourse about police violence in the city of Porto Alegre. At first, it was made a research to collect data on police violence in Brazil in order to demonstrate the relevance of the problem, and also a demonstration about some sociological and criminological contributions that could help on the understanding of the topic. Secondly, it was showed the data collected during the empirical research from the analysis of some police investigations and criminal prosecution of homicide crimes practiced by police officers. Finally, the methodology of discourse analysis was used to demonstrate the regularities that are present in the discourse of the police authorities and public prosecutors in the specific cases of lethal police violence that were analyzed here, using the subcultural theory and the neutralization theory to help on the comprehension of the topic.